Introduction into the Marseille geographical area of a mild SARS-CoV-2 variant originating from sub-Saharan Africa: An investigational study. Issue 40 (March 2021) - Colson, Philippe; Levasseur, Anthony; Gautret, Philippe; Fenollar, Florence; Thuan Hoang, Van; Delerce, Jeremy; Bitam, Idir; Saile, Rachid; Maaloum, Mossaab; Padane, Abdou; Bedotto, Marielle; Brechard, Ludivine; et al.
Abstract: Background: In Marseille, France, the COVID-19 incidence evolved unusually with several successive epidemic phases. The second outbreak started in July, was associated with North Africa, and involved travelers and an outbreak on passenger ships. This suggested the involvement of a new viral variant. Methods: We sequenced the genomes from 916 SARS-CoV-2 strains from COVID-19 patients in our institute. The patients' demographic and clinical features were compared according to the infecting viral variant. Results: From June 26th to August 14th, we identified a new viral variant (Marseille-1). Based on genome sequences (n = 89) or specific qPCR (n = 53), 142 patients infected with this variant were detected. It is characterized by a combination of 10 mutations located in the nsp2, nsp3, nsp12, S, ORF3a, ORF8 and N/ORF14 genes. We identified Senegal and Gambia, where the virus had been transferred from China and Europe in February–April as the sources of the Marseille-1 variant, which then most likely reached Marseille through Maghreb when French borders reopened. In France, this variant apparently remained almost limited to Marseille. In addition, it was significantly associated with a milder disease compared to clade 20A ancestor strains, in univariate analysis. Conclusion: Our results demonstrate that SARS-CoV-2 can genetically diversify rapidly, its variants can diffuse internationally and cause successive outbreaks.